The Effect Different Young Coconut Water in NaCl On Spermatozoa Quality Of Catfish (Clarias gariepinus) During Short Storage - Hardini Rika Pangaribuan; Sukendi Sukendi; Hamdan Alawi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThis research was conducted in September 2019 in the fish hatchery and breeding laboratory of the Faculty of Fisheries and Marine of Riau University and Photomocrography laboratory of Mathematics sand Natural Sciences Faculty, Riau  University. The purpose of this study was to evaluate the effect of different in the concentration of  young coconut water on NaCl on sperm motility, viability, fertility, and hatching rates of catfish (Clarias gariepinus) during short storage. This study used a Completely Randomized Design (CRD), with 5 levels of treatment and 3 replications, namely: P0: 0%  young coconut water plus 100% NaCl (Control), P1: 40%  young coconut water plus 60% NaCl, P2 : 50% young water plus 50% NaCl , P3: 60% young coconut water plus 40% NaCl, P4: 70% young coconut water plus 30% NaCl. Semen of this experiment used from 2 male catfish, and was stored  in the refrigerator at 40C . The results showed that the different of  young coconut water concentration in NaCl had a  significant effect on the sperm quality of catfish (Clarias gariepinus) for 96 hours at 12 hour intervals. The results showed that P4 (70% young coconut water plus 30% NaCl solution) was the best treatment with 72 hours optimal storage times with good category (3) with a viability percentage of 51.4%, fertilization rate at 12 hours storage period reached 89.0% with hatching rate 88.5% while at 96 hours fertilization rate is 50.4%, and hatching rate is 78.9%Keywords: Clarias gariepinus, young coconut water, NaCl, qualityof spermatozoa.